(untitled) (Texas Journal of Medical Science, 2024)
Chronic trophic ulcers of the foot and the tibia affect up to 2% of the working population of industrially developed countries. In our scientific work we experimentally examined the effectiveness of wound healing with the use of modern tissue engineering construction collagen enriched with fibroblasts in modeled trophic ulcer in rats of the genus Wistar.